Class II phosphoinositide 3-kinase regulates exocytosis of insulin granules in pancreatic ß cells - Dominguez, V.; Raimondi, C.; Somanath, S.; Bugliani, M.; Loder, M.; Edling, C.; Divecha, N.; Silva-Xavier, G.; Marselli, L.; Persaud, S.; Turner, M.; Rutter, G.; et al. (2011)
Phosphoinositide 3-kinases (PI3Ks) are critical regulators of pancreatic ß cell mass and survival, whereas their involvement in insulin secretion is more controversial. Furthermore, of the different PI3Ks, the class II isoforms were detected in ß cells, although their role is still not well understood. Here we show that down-regulation of the class II PI3K isoform PI3K-C2a specifically impairs insulin granule exocytosis in rat insulinoma cells without affecting insulin content, the number of insulin granules at the plasma membrane, or the expression levels of key proteins involved in insulin secretion. Proteolysis of synaptosomal-associated protein of 25 kDa, a process involved in insulin granule exocytosis, is impaired in cells lacking PI3K-C2a. Finally, our data suggest that the mRNA for PI3K-C2a may be down-regulated in islets of Langerhans from type 2 diabetic compared with non-diabetic individuals. Our results reveal a critical role for PI3K-C2a in ß cells and suggest that down-regulation of PI3K-C2a may be a feature of type 2 diabetes.